Depiction of Shiva as Gajantak - Temples of India Project Team (Jio Institute, 2024)
Housed in the Government Museum, Sikar, it is identified as the figure ’Killing of Asavathama elephant by Pandava prince, Bhima’ on the label. However, the identification has little support beyond speculation. Given the size of the figure and its delicate rendition, another speculation arises, suggesting it may depict Shiva as Gajantak, the killer of the demon elephant.